Perbandingan Litigasi dan Alternative Dispute Resolution (ADR) dalam Penyelesaian Sengketa Bisnis di Indonesia (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines the comparison between litigation and Alternative Dispute Resolution (ADR) in resolving business conflicts in Indonesia. The increasingly complex nature of business activities has led to a variety of conflicts, such as breach of contract, share ownership disputes, and payment issues, which require efficient resolution methods that provide legal certainty. This study aims to explore the characteristics, procedures, advantages, and disadvantages of dispute resolution through litigation and ADR, which include negotiation, mediation, conciliation, and arbitration. The method applied is normative juridical, drawing on legislation, legal doctrine, and relevant literature. The research findings indicate that litigation offers stronger legal certainty through binding court decisions and organized procedures, but is often time-consuming, expensive, and produces win-lose outcomes. On the other hand, ADR offers flexibility, confidentiality, efficiency, and the opportunity to reach mutually beneficial solutions, although in some situations it requires court confirmation for enforcement. Therefore, the choice of dispute resolution method needs to be adjusted to the nature of the conflict, the relationship between the parties, and the need for legal certainty.